Suicidal chemotaxis in bacteria - Oliveira, NM; Wheeler, JHR; Deroy, C; Booth, SC; Walsh, EJ; Durham, WM; Foster, KR (Springer Nature, 2022)
Bacteria commonly live in surface-associated communities where steep gradients of antibiotics and other chemical compounds can occur. While many bacterial species move on surfaces, we know surprisingly little about how such antibiotic gradients affect cell motility. Here, we study the behaviour of the opportunistic pathogen Pseudomonas aeruginosa in stable spatial gradients of several antibiotics by tracking thousands of cells in microfluidic devices as they form biofilms. Unexpectedly, these experiments reveal that bacteria use pili-based (‘twitching’) motility to navigate towards antibiotics. Our analyses suggest that this behaviour is driven by a general response to the effects of antibiotics on cells. Migrating bacteria reach antibiotic concentrations hundreds of times higher than their minimum inhibitory concentration within hours and remain highly motile. However, isolating cells - using fluid-walled microfluidic devices - reveals that these bacteria are terminal and unable to reproduce. Despite moving towards their death, migrating cells are capable of entering a suicidal program to release bacteriocins that kill other bacteria. This behaviour suggests that the cells are responding to antibiotics as if they come from a competing colony growing nearby, inducing them to invade and attack. As a result, clinical antibiotics have the potential to lure bacteria to their death.